The Influence of Emotional Intelligence on Student Learning Motivation - Lulu Latifah; Tugimin Supriyadi (Syntax Corporation Indonesia, 2024)
This research aims to identify the influence of emotional intelligence on the learning motivation of students in the Arabic Language Education study program at Jakarta State University. Using quantitative methods and a correlational approach, this research involved 116 respondents from two cohorts (2022 and 2023). The research results show that there is a significant positive relationship between emotional intelligence and student learning motivation. Data were analyzed using statistical techniques such as regression tests and Pearson correlation with the help of IBM SPSS Statistics 24 software. The results showed that emotional intelligence contributed 31.3 % to learning motivation, while other variables also influenced students' overall learning motivation. It is hoped that this research can provide a deeper understanding of the factors that influence student learning motivation, as well as provide a basis for developing more effective educational strategies in the future.